Ответы и объяснения

2013-04-28T16:53:10+04:00

3)Преобразуем выражение:

4(a-c)+a(c-a)=4(a-c)-a(a-c)=(4-a)(a-c)

Подставим значения:

(4-3.5)(3.5+1.5)=0.5*5=2.5

2013-04-28T17:30:21+04:00

1. Разложите на множители  

а) 6a² + ab - 5a = a ( 6a + b - 5)

б) 7x²y - xy² = xy (7x - 1)

в) 12c³ + 4c² = 4c²(3c + 1)

г) 3x (x + 2)  - 2(x+2) = (x+2)(3x - 2)

д) ab + 2ac + 2b + 4c = a(b + 2c) + 2 (b +2c) = (b + 2c)(a + 2)

 

2. Представьте в виде произведения

а) 3x²y  + 6x²y² + 3x³y² = 3x²y (1 + 2y + 3xy)

б) x²(1-x) + x(x-1)² = x²(1-x) + x(1-x)² = x(1-x)(x+1-x) = x(1-x)

в) 2a + ab - 2b - b² = a (2 + b) - b (2 + b) = (2+b)(a-b)

г)  5a - 5b - xa + xb - b + a = 5(a-b) - x(a-b) + (a-b) = (a-b)(5-x+1) = (a-b)(6-x)

 

3. Найдите значение выражения при а = 3,5    и    c = -1,5

4a - 4c + ac - a² = 4(a-c) - a(a-c) = (a-c)(4-a) = (3,5 + 1,5)(4 - 3,5) = 5 · 0,5 = 2,5